Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.9775/kvfd.2014.12484
|View full text |Cite
|
Sign up to set email alerts
|

Doğu Anadolu’da Van Gölü Havzası Çevresinde Bulunan Çeşitli Yabani Kuş Türlerinde Saptanan Çiğneyici Bit (Phthiraptera: Amblycera, Ischnocera) Türleri

Abstract: This study was performed to detect chewing lice on the wild birds in Eastern Turkey, between April 2013-September 2014. 108 injured birds brought to Wild Animal Protection Center of Yüzüncü Yıl University were examined for louse. The feathers of each bird specimens were inspected for louse, macroscopically. Collected lice samples on the birds were preserved in 70% ethyl alcohol and mounted on slides in Canada balsam after transparented in 10% KOH. Fifteen (14.95%) out of the 108 were found to be infested with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Discussion Lice infesting eagles have been documented in many parts of the world (e.g., Emerson 1972;Tuggle and Schmeling 1982;Smithers et al 1996;Price et al 2003;Göz et al 2015;Tomás et al 2016); however, quantitative data are seldom gathered on the ectoparasites of bald eagles. Bald eagles are large and awkward to handle.…”
Section: Resultsmentioning
confidence: 99%
“…Discussion Lice infesting eagles have been documented in many parts of the world (e.g., Emerson 1972;Tuggle and Schmeling 1982;Smithers et al 1996;Price et al 2003;Göz et al 2015;Tomás et al 2016); however, quantitative data are seldom gathered on the ectoparasites of bald eagles. Bald eagles are large and awkward to handle.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies done relevant to the chewing lice found on wild birds, approximately 100 lice species have been detected in the birds in Turkey, until today. This species have been reported from Greylag Goose (Anser anser) in Van [18] and Wild Swans in Samsun, Turkey [10] . T. anserinum was recorded from Whooper Swan (Cygnus cygnus) for the first time in this study, in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Because all lice species were described under the genus Aegypoecus found on Vulturidae, Buteo rufinus may be accepted as a natural host for this new louse species. Indeed there are few studies about louse species of the wild birds in Turkey although on intercontinental route of migratory birds [7][8][9][10] . …”
Section: Genitalia Is Displayed Inmentioning
confidence: 99%